Congruity (li) as ethical notion in Zhu Xi’s theory of renxing - Silius, Vytis (Acta Orientalia Vilnensia, 2010)
Vilnius University This article deals with the cosmology and ethics of Zhu Xi (朱熹) and reconstructs the relation between these two fields of inquiry in Zhu Xi’s philosophy. This article opposes the still common view in contemporary scholarship that portrays Zhu Xi as a metaphysical thinker who introduced metaphysical notions into the Confucian discourse. The true originality and innovation of Zhu Xi was his attempt to appropriate the notion of li 理, which was the key term in the metaphysical speculations of Chinese Buddhism and was also adopted by the early Song neo-Confucians in their cosmological investigations, and to show its relevance and conformity to the classical Confucian ethical thought. The article demonstrates how Zhu Xi turns li 理 into a key ethical concept through identifying it with the particular course of the growth (xing 性) of things and ultimately, with the particular course of human growth (renxing 人性).